Mass Spectrometry for O-GlcNAcylation - Yin, Ruoting; Wang, Xin; Li, Cheng; Gou, Yuhan; Ma, Xuecheng; Liu, Yongzhao; Peng, Jianfang; Wang, Chao; Zhang, Ying (Frontiers in Chemistry, 2021)
O-linked β-N-acetylglucosamine modification (O-GlcNAcylation), one universal post-translational modification commonly found in nuclear and cytoplasmic proteins, shows regulatory roles in a variety of biological processes, such as signal transduction, transcriptional regulation, stress response, etc. Moreover, O-GlcNAcylations with abnormal expression levels have proven to be associated with many diseases including Alzheimer, diabetes and tumor. Therefore, sensitive O-GlcNAcylation profiling is of great importance for structure-function mechanism elucidating of low-abundance O-GlcNAcylated protein with high heterogeneity as required for glycomics. Mass spectrometry (MS) with high sensitivity and throughput properties has become widely used for comprehensive characterization of O-GlcNAcylation, enabling in-depth understanding of their biological roles these years. Herein, this review provides a comprehensive update of MS-based methodologies for quali-quantitative characterizing of O-GlcNAcylation.